Provision of Social Goods and Soft Budget Constraints - Zhentang Zhang; Lars-Hendrik Röller (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Firms in socialist and transitional economies are often obliged to provide a social good in addition to a private good, which makes it difficult for a government to commit not to bail out the firm once it is in financial trouble. This creates a soft budget constraint syndrome which causes the firm to underinvest ex ante in order to extract state subsidy and thereby reduces dynamic efficiency. In this paper, we show that separating the provision of social goods from private goods can harden budget constraints, while introducing competition into the private market may not.
Keywords: 330; Betriebliche Sozialleistungen; Budgetrestriktion; Übergangswirtschaft; Reorganisation; Theorie der Unternehmung; Public Choice